-12x+3=-8x-6

Simple and best practice solution for -12x+3=-8x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12x+3=-8x-6 equation:


Simplifying
-12x + 3 = -8x + -6

Reorder the terms:
3 + -12x = -8x + -6

Reorder the terms:
3 + -12x = -6 + -8x

Solving
3 + -12x = -6 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
3 + -12x + 8x = -6 + -8x + 8x

Combine like terms: -12x + 8x = -4x
3 + -4x = -6 + -8x + 8x

Combine like terms: -8x + 8x = 0
3 + -4x = -6 + 0
3 + -4x = -6

Add '-3' to each side of the equation.
3 + -3 + -4x = -6 + -3

Combine like terms: 3 + -3 = 0
0 + -4x = -6 + -3
-4x = -6 + -3

Combine like terms: -6 + -3 = -9
-4x = -9

Divide each side by '-4'.
x = 2.25

Simplifying
x = 2.25

See similar equations:

| (k+4)=7 | | -2(3+4m)=-18 | | 22=-6-2r | | 10-7n=-25 | | y=2.22x+4.40 | | 35=-7(3+t) | | (-3xy)(7xy)= | | 14n+q=rt-4n | | -10+9x=125 | | 3x+48=2x+24 | | 40x+9.6x=644.80 | | 0=-(x-3)(x-3)+1 | | 5.50(h)=71.50 | | 5w-4w+2w=9 | | 3x+9-9(x+1)=2x+5 | | -5/12*27/15= | | 12+5x=68 | | 15y+17=13y+14 | | 2x-6=5x+22 | | 40-14x=21x-100 | | 0.10+0.05(52-x)=4.50 | | 7=6m-2m+3 | | 7x(6+8)=7*6+7x | | 16x-6153=1143 | | 4(4x-7)(2x+7)=0 | | 170+106+17x=1600 | | x+-4+2x=1 | | s-10=20.68 | | 4x-84=9x+3 | | 8-4u=8u-5 | | 86x+9648=48090 | | -39=-18w-21 |

Equations solver categories